Medication adherence and real-world factors of first line induction treatment selection in ANCA-associated vasculitis - Akyüz Dağlı, Pınar; Erdoğan, Esra Kayacan; Konak, Hatice Ecem; Özdemir Ulusoy, Bahar; Güven, Serdar Can; Armağan, Berkan; Koçak Ulucaköy, Rezan; Orhan, Kevser; Atalar, Ebru; Doğan, İsmail and Maraş, Yüksel and Omma, Ahmet and Küçükşahin, Orhan and Erten, Şükran and Babaoğlu, Hakan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background & Objective: This study aimed to explore real-world factors that may influence the selection of first-line remission-induction therapy in ANCA-associated vasculitis(AAV), as well as to evaluate physician compliance with guideline recommendations and patient adherence to maintenance therapies. Methods: A retrospective analysis of 112 patients with AAV, including granulomatosis with polyangiitis(GPA, 67%), microscopic polyangiitis(MPA, 13%),and eosinophilic granulomatosis with polyangiitis (EGPA, 20%), was conducted at a single tertiary care center using electronic health records from 2018 to 2023. Treatment regimens, patient demographics, organ involvement, and adherence to EULAR guidelines were analyzed.Patients receiving RTX or CYC as first-line remission-induction therapy were compared.Compliance was defined as alignment with guideline-recommended dosing and timing of induction therapy, while adherence during maintenance was evaluated based on consistency with prescribed regimens, assessed via prescription refill data. Results: Of the 102 patients included in the study, 85 received CYC and 17 received RTX as first-line remission induction therapy.Compared to the RTX group, those receiving CYC were significantly older (median age 57 vs. 44 years, p <0.05), had higher BVAS scores (median 12 vs. 10, p = 0.02), and exhibited more comorbidities (74% vs. 35%). Organ involvement rates were similar in both groups. No significant differences in major organ involvement were observed between the two groups. RTX adherence was 100% in both the induction and maintenance phases, whereas adherence to oral maintenance therapies was notably lower, at 66% for methotrexate, 36% for mycophenolate mofetil, and 28% for azathioprine. Conclusion: In real-world practice, older age, higher BVAS, and a greater comorbidity burden appear to influence clinicians’ preference for CYC over RTX as first-line induction,despite similar organ involvement between groups.Overall compliance with induction guidelines was high,but adherence to oral maintenance regimens remained suboptimal.These findings underscore the need for personalized treatment strategies and targeted measures to enhance long-term medication adherence in AAV.